MENYIASATI RUANG, MENEBAR KEDAMAIAN - Dedi Slamet Riyadi (Harmoni, 2017)
To me, its nonsense—and very dangerous nonsens at that—all this talk of I’m Tajik and you’re Pashtun and he’s Hazara and she’s Uzbek. We’re all afghans, and that’s all that should matter. But when one group rules over the others for so long … there’s contempt. Rivalry. There is. There always have been. (Khaled Hosseini, A Thousand Splendid Suns)[1] [1] Khaled Hosseini, A Thousand Splendid Suns, Bloomsbury Publisihing, London, 2007, hlm. 117.